Pemanfaatan Teknologi AI untuk Inovasi dan Efisiensi di Era Digital dengan Memperhatikan Kelebihan, Kekurangan, dan Dampaknya bagi Siswa/i SMP Sebelas Maret - Kaila Nazuwa; Adis Tiani; Helmayana; Intan Pramesta Nurhayati; Yuriana Sari Harahap (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2025)
Artificial intelligence (AI) technology has opened many doors in the world of education, especially to improve efficiency and innovation in the teaching and learning process. The purpose of this study is to see how artificial intelligence technology is used by students of SMP Sebelas Maret. The study will explore the benefits, disadvantages, and effects produced. Educational chatbots, adaptive learning applications, and automated assessment tools are all examples of AI used to assist teachers and meet students' specific learning needs. The results of the study indicate that the main advantages of using AI lie in the ability to present customizable and interactive materials, increase the desire to learn, and increase time efficiency in learning management. However, there are some disadvantages, such as dependence on technology, students' lack of understanding of digital ethics, and the potential for reduced social interaction. Students of SMP Sebelas Maret experienced a significant impact, with improved learning outcomes and a shift towards more independent learning. To ensure that the use of AI does not cause problems or adverse effects in the long term, adequate digital literacy and mentoring are needed. In conclusion, AI has great potential to be an effective tool to support educational transformation in the digital era. However, it must be used carefully, adaptively, and contextually to meet the readiness of the educational environment. The study found that teachers need to be better trained and that policies for the use of AI in junior high schools need to be made targeted and sustainable.